2020
DOI: 10.1088/1757-899x/982/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network (CNN) for Automatic Skin Cancer Classification System

Abstract: Skin cancer is a type of cancer that grows in the skin tissue, which can cause damage to the surrounding tissue, disability, and even death. In Indonesia, skin cancer is the third leading for most cancer cases after cervical and breast cancer. The accuracy of diagnosis and the early proper treatment can minimize and control the harmful effects of skin cancer. Due to the similar shape of the lesion between skin cancer and benign tumor lesions, physicians consuming much more time in diagnosing these lesions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 4 publications
0
27
0
1
Order By: Relevance
“…Öğrenme işlemi, filtre katsayıları ve katmanlar arası ağırlık değerlerinin veriyi temsil eden uzayında optimum olarak belirlenmesiyle gerçekleşmektedir. Çalışmamızda, optimum çözüme ulaşmada iyi performans gösteren Adam optimizasyon algoritması, öğrenme algoritması olarak seçilmiştir [35].…”
Section: Optimizasyon Algoritması (Optimization Algorithm)unclassified
“…Öğrenme işlemi, filtre katsayıları ve katmanlar arası ağırlık değerlerinin veriyi temsil eden uzayında optimum olarak belirlenmesiyle gerçekleşmektedir. Çalışmamızda, optimum çözüme ulaşmada iyi performans gösteren Adam optimizasyon algoritması, öğrenme algoritması olarak seçilmiştir [35].…”
Section: Optimizasyon Algoritması (Optimization Algorithm)unclassified
“…This network structure consists of several convolution layers, a pooling layer including max pooling or mean pooling and a fully connected layer [30]- [32]. Several medical applications that apply the CNN network model include brain tumor detection [33], breast cancer classification [34], skin diseases [35], and cardiovascular disease [36].…”
Section: Image Processing (Normalization)mentioning
confidence: 99%
“…In this paper [14], the authors implied a custom CNN based method to predict skin cancer from pictures. In this paper [11], an automated system is proposed by the authors to identify the situations of di↵erent types of skin cancers from digital image processing. However the CNN model is adopted in this paper [11] containing 3 hidden layers which uses 3×3 filter sizes with 16, 32, and 64 channel outcomes in cycle and has a completely connected layer and softmax activation.…”
Section: Documentation Outlinementioning
confidence: 99%
“…In this paper [11], an automated system is proposed by the authors to identify the situations of di↵erent types of skin cancers from digital image processing. However the CNN model is adopted in this paper [11] containing 3 hidden layers which uses 3×3 filter sizes with 16, 32, and 64 channel outcomes in cycle and has a completely connected layer and softmax activation. They have conducted their optimization utilizing Adam, SGD, RMSprop, and Nadam optimizer on their proposed model and eventually based on their testing the authors found that the Adam optimizer gives the best interpretation of skin cancer lesions with 99% of accurateness from the dataset with the number of precision, recall and F1-is nearly 1.…”
Section: Documentation Outlinementioning
confidence: 99%